2006
DOI: 10.1088/0029-5515/46/10/005
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the 16th IAEA Technical Meeting on ‘Research using Small Fusion Devices’

Abstract: Common research topics that are being studied in small, medium and large devices such as H-mode like or improved confinement, turbulence and transport are reported. These included modelling and diagnostic developments for edge and core, to characterize plasma density, temperature, electric potential, plasma flows, turbulence scale, etc. Innovative diagnostic methods were designed and implemented which could be used to develop experiments in small devices (in some cases not possible in large devices due to high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In Fig. 5 (PF-1000, IPPLM, Poland) one may see a set of oscilloscope traces taken in a single shot by means of a number of diagnostics [5].…”
Section: Experiments In Dmp Physicsmentioning
confidence: 99%
“…In Fig. 5 (PF-1000, IPPLM, Poland) one may see a set of oscilloscope traces taken in a single shot by means of a number of diagnostics [5].…”
Section: Experiments In Dmp Physicsmentioning
confidence: 99%
“…An essential contribution to the studies of neutron production has recently been made by an international group of scientists in the PF-1000 facility [27][28][29][30]. The main goal of these studies is the search for an answer to a key question: is the observed saturation in the neutron yield caused by the incorrect formation of a proper plasma sheath for many reasons (e.g.…”
Section: Studies Of Neutron Radiation On Pf-1000 Facilitymentioning
confidence: 99%
“…Maximal heat loads expected in FRs with magnetic plasma confinement (MPC) are about 10 4 W cm −2 whereas in reactors with inertial plasma confinement (IPC) these figures may reach up to 10 8 W cm −2 . The dense plasma focus (DPF) device can not only ensure the fulfilment of the values of the loads much higher compared with the above-mentioned ones but it can produce it namely with the same load carriers (hot plasma and fast particles) having the same parameters expected on the plasma-facing components of the contemporary main-stream fusion devices (like ITER and NIF) [3].…”
Section: Introductionmentioning
confidence: 99%